League of denial : the NFL's concussion crisis [videorecording (DVD)] - Kirk, Michael; Fainaru-Wada, Mark (PBS, 2013)
Examines the realities of brain injuries sustained on the field by football players and the National Football League's attempts to cover the issue up.